Intensified and Accelerated Rescue Infliximab Therapy for Acute Severe Ulcerative Colitis in Pregnancy: A Case Report - Saiumaeswar Yogakanthi; Timothy Phan; Emma Flanagan; Linda Yang; Chamara Basnayake; Iniyaval Thevathasan; Julien Schulberg (JGH Open)
ABSTRACT Acute severe ulcerative colitis (ASUC) in pregnancy poses a clinical challenge with significant risk to both mother and fetus. Anti‐TNF alpha therapy is known to be safe in pregnancy, however, data surrounding outcomes in ASUC is limited. In this report, we present the case of a pregnant patient of 10 weeks' gestation with ASUC successfully managed with intensified and accelerated infliximab therapy for a total dose of 35 mg/kg during a single admission. This case highlights the use of this therapeutic strategy, as a part of a multidisciplinary approach, to avoid the need for a high‐risk colectomy.